Four broad temperament dimensions: description, convergent validation correlations, and comparison with the Big Five - Fisher, Helen E.; Island, Heide D.; Rich, Jonathan; Marchalik, Daniel; Brown, Lucy L. (Frontiers in Psychology, 2015)
A new temperament construct based on recent brain physiology literature has been investigated using the Fisher Temperament Inventory (FTI). Four collections of behaviors emerged, each associated with a specific neural system: the dopamine, serotonin, testosterone and estrogen/oxytocin system. These four temperament suites have been designated: 1) Curious/Energetic, 2) Cautious/Social Norm Compliant, 3) Analytical/Tough-minded, and 4) Prosocial/Empathetic temperament dimensions. Two functional magnetic resonance imaging (fMRI) studies have suggested that the FTI can measure the influence of these neural systems. In this paper, to further the behavioral validation and characterization of the four proposed temperament dimensions, we measured correlations with five variables: 1) gender; 2) level of education; 3) religious preference; 4) political orientation; 5) the degree to which an individual regards sex as essential to a successful relationship. Subjects were 39,913 anonymous members of a US Internet dating site and 70,000+ members in six other countries. Correlations with the five variables characterize the Fisher Temperament Inventory and are consistent with mechanisms using the proposed neuromodulators. We also report on an analysis between the FTI and the NEO-Five Factor Inventory, using a college sample (n=215), which showed convergent validity. The results provide novel correlates not available in other questionnaires: religiosity, political orientation and attitudes about sex in a relationship. Also, an Eigen analysis replicated the four clusters of co-varying items. The FTI, with its broad systems and non-pathologic factors complements existing personality questionnaires. It provides an index of some brain systems that contribute to temperament, and may be useful in psychotherapy, business, medicine, and the legal community.